2007
DOI: 10.1002/jbm.b.30721
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel‐filled polylactide porous scaffolds for cartilage tissue engineering

Abstract: Polymer porous scaffolds and hydrogels have been separately employed as analogues of the native extra-cellular matrix (ECM). However, both of these two kinds of materials have their own advantages and shortcomings. In this work, an attempt to combine the advantages of these two kinds of materials is carried out. Poly-L-lactide (PLLA) scaffolds with good mechanical properties were prepared by thermally induced phase separation, which were then filled with hydrogel aiming at entrapment of cells within a support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 105 publications
(135 reference statements)
1
57
0
1
Order By: Relevance
“…22,24,52,53 Unfortunately, these methods fail to provide information on the location, distribution, and infiltration of cells into constructs. In fact, early research conducted for each seeding method showed little variation, with efficiencies of approximately 50%, consistent with unmodified PLGA saltleached scaffolds using these methods, although in disagreement with analysis of the sections of the scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…22,24,52,53 Unfortunately, these methods fail to provide information on the location, distribution, and infiltration of cells into constructs. In fact, early research conducted for each seeding method showed little variation, with efficiencies of approximately 50%, consistent with unmodified PLGA saltleached scaffolds using these methods, although in disagreement with analysis of the sections of the scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the round shaped cells that often take upon gel encapsulation, which has been shown to be beneficial for the chondrogenic phenotype. 51 However, when studying the influences of cocultures on matrix production, hydrogels may potentially restrict the dispersion of cells and secreted factors and thus alter the effects of coculture. 52 For this reason, this study set forth to examine the interaction of chondrocytes and MSCs in a highly porous, fibrous scaffold focusing on the production of the ECM within the scaffold.…”
Section: Levorson Et Almentioning
confidence: 99%
“…Most importantly, the matrix needs to have a three-dimensional (3-D) structure with high porosity, but at the same time, maintaining a normal tensile strength. A 3-D scaffold with higher porosity and relative larger pore size (50-200 mM) promotes cell proliferation, migration and infiltration into the matrix, and appears to allow abundant cell loading onto the scaffold, thereby promoting in vivo tissue regeneration and wound healing [23][24][25][26]. Such a scaffold would also allow the host cells to participate in the tissue remodeling processes by infiltration or migration into the matrix from the wound edges.…”
Section: Introductionmentioning
confidence: 97%